Proceedings of the 2nd International Conference of Business, Accounting and Economics, ICBAE 2020, 5 - 6 August 2020, Purwoker 2020
DOI: 10.4108/eai.5-8-2020.2301187
|View full text |Cite
|
Sign up to set email alerts
|

Micro Small Medium Enterprises (MSMEs) Survival Ability in Pandemic Covid 19 Era: Integration of Technology, Organization, and Environment Analysis

Abstract: The Pandemic of COVID-19 has economic, social and political implications not only for large countries but also for almost all countries in the world. Indonesia is one of the countries affected mainly from the economic side, which is dominated by Micro, Small and Medium Enterprises (MSMEs). The economic slowdown occurred, requires companies to have a clear understanding of the crisis occurred to ensure they more quickly adapt to the situation and minimize the company's losses. One way is to apply digital techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…, 2021). Digital technology has the potential to benefit MSMEs (Arinta et al. , 2020; Fitriasari, 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2021). Digital technology has the potential to benefit MSMEs (Arinta et al. , 2020; Fitriasari, 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The continuous survival of small businesses requires managers to enhance flexible approaches and contingent strategic decision-making (Hafiz et al, 2021). Digital technology has the potential to benefit MSMEs (Arinta et al, 2020;Fitriasari, 2020). Pu et al (2021) conducted a study on SMEs in Bangladesh and found that integrating technological adaptation and innovative finance in the business strategy can help small businesses in accelerating the sustainability of firms.…”
Section: Firm Revival Strategies and Firm Sustainabilitymentioning
confidence: 99%
“…Technology adoption during the pandemic helped the firms in improving their performance and sustainability through procurement with lower cost and better relationships with the supplier (Evangelista and Hallikas, 2022;Do et al, 2020;Verma et al, 2017), online selling (Reniati et al, 2019), differentiation in products and service delivery (Mohan and Ali, 2019), better supply chain performance (Shiralkar et al, 2021;Kumar et al, 2017Kumar et al, , 2022cPathak et al, 2020Pathak et al, , 2021, managing relationship with the customer (Chi, 2021), high customer satisfaction (Cuevas-Vargas et al, 2022). Literature provides evidence that ICT adoption has offered benefits to almost all businesses irrespective of their size and nature (Arinta et al, 2020;Pu et al, 2021;Chaudhary et al, 2020a, b;Kumar and Ayedee, 2021). Thus we hypothesized that ICT adoption during and following the COVID 19 pandemic does not differ significantly from the nature of the industry.…”
Section: Nature and Impact Of The Msme Sectormentioning
confidence: 99%